MntP and YiiP Contribute to Manganese Efflux in Salmonella enterica Serovar Typhimurium under Conditions of Manganese Overload and Nitrosative Stress - Annie Ouyang; Kendall M. Gasner; Stephanie L. Neville; Christopher A. McDevitt; Elaine R. Frawley (Microbiology Spectrum, 2022)
ABSTRACT The divalent transition metal cation manganese is important for protein function, particularly under conditions of iron limitation, nitrosative stress, and oxidative stress, but can mediate substantial toxicity in excess. Salmonella enterica serovar Typhimurium possesses multiple manganese importers, but the pathways for manganese efflux remain poorly defined. The S. Typhimurium ATCC 14028s genome was analyzed for putative manganese export pathways, which identified a previously uncharacterized homologue of the Escherichia coli manganese exporter mntP, stm1834, and two cation diffusion facilitator family transporters, zitB (stm0758) and yiiP (stm4061). Manganese acquisition by S. Typhimurium has been shown to occur in response to nitric oxide, an important chemical mediator of the mammalian innate immune response. However, cellular manganese can rapidly return to prechallenge levels, strongly suggesting that one or more S. Typhimurium exporters may contribute to this process. Here, we report that mntP and yiiP contribute to manganese resistance and export in S. Typhimurium. YiiP, also known as FieF, has previously been associated with zinc and iron transport, although its physiological role remains ambiguous due to a lack of zinc-sensitive phenotypes in yiiP mutant strains of S. Typhimurium and E. coli. We report that S. Typhimurium ΔmntP ΔyiiP mutants are exquisitely sensitive to manganese and show that both YiiP and MntP contribute to manganese efflux following nitric oxide exposure. IMPORTANCE Transition metal cations are required for the function of many proteins but can mediate toxicity when present in excess. Identifying transporters that facilitate metal ion export, the conditions under which they are expressed, and the role they play in bacterial physiology is an evolving area of interest for environmental and pathogenic organisms. Determining the native targets of metal transporters has proved challenging since bioinformatic predictions, in vitro transport data, and mutant phenotypes do not always agree. This work identifies two transporters that mediate manganese efflux from the Gram-negative pathogen Salmonella enterica serovar Typhimurium in response to manganese overload and nitric oxide stress. While homologues of MntP have been characterized previously, this is the first observation of YiiP contributing to manganese export.